COHERENCE IN LOGICAL THINKING: A CONVERSATION ANALYSIS - Azwar Abidin (Indonesian Journal of Basic Education, 2019)
This article examines the extent of the individuals’ coherence in logical thinking and the way the concepts or ideas are linked together and bringing consistence in maintaining meaning-make sense in live interview session. The scope of this article is restricted to the identification of logical thinking pattern in conversation. The analysis is limited to the particular individuals with particular topics in conversation. The coherence is identified through the concepts that link one another which maintain the logical pattern of stored information. It may result projection of linking concepts that are maintained along the conversation and the way language use may trick someone